A Finite-Difference Scheme for the Generalized Diffuse Interface Model of the Electrical Breakdown Process - Ponomarev, A. S.; Zipunova, E. V. (Mathematical models and computer simulations, 2024)
The subject of the present work is numerical studies of a generalization of a diffuse interface model describing the development of the electrical breakdown channel. The Allen–Cahn type equation governing the phase field evolution is a nonlinear partial differential equation including 4th order terms. The solutions of this equation may have singular behavior in some cases. In the paper, we propose a new finite-difference scheme allowing an exact accounting of the singularities of the solution and its accurate computation, even in the case when the boundary conditions are defined on objects of higher codimension.